STRUKTUR KOMUNITAS MAKROALGA DI PANTAI GEGER DAN PANTAI MENGENING KABUPATEN BADUNG - Maharani, Ni Putu Sintha; Watiniasih, Ni Luh; Dewi, Ayu Putu Wiweka Krisna (SIMBIOSIS; Vol 9 No 1 (2021)DO - 10.24843/JSIMBIOSIS.2021.v09.i01.p06, 2021)
Macroalgae is a type of flora known as seaweed and is classified into low-level plants, where roots, stems, and leaves are relatively difficult to distinguish. This study aims to determine the differences of habitat characteristics, number of species, biomass, and macroalgae community structure in Geger Beach and Mengening Beach. This quadrant transect method was used to collect the data. The results show that Geger Beach has sandy substrate, while Mengening Beach has substrate consisting of coral rock. The water quality in both locations are still suitable for macroalgae growth. The results of the study found 8 types of macroalgae in Geger Beach and 10 types of macroalgae in Mengening Beach. The highest macroalgae biomass at Geger Beach was found in Gracilaria hayi with the weight ranging from 72.08-73.18 g/m 2 , while at Mengening Beach was found in the Valonia aegagropila , ranging from 181.31-190.40 g/m 2 . The diversity index of macroalgae in Geger Beach was between 1.93-1.99, while at Mengening Beach was between 1.79-2.07, therefore categorized as medium. The dominance index of macroalgae at Geger Beach was between 0.15-0.17, while at Mengening Beach was between 0.17-0.25, therefore the dominance index at both site was categorized low. The evenness index at Geger Beach was between 0.93-0.96, while at Mengening Beach was between 0.78-0.90, which categorized as stable conditions.